Implementation of Moral Aqidah Learning on Student Discipline - Mawaddah, Nurul (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This article examines the impact of the implementation of moral aqidah learning outcomes on student discipline. The problem in this paper is: how is the subject of Aqidah Akhlak taught at MTs Daarul Qur'an Pajalele, Tellusiatinge District, Bone Regency? How is the discipline in the class of students at MTs Daarul Qur'an Pajalele, Tellusiatinge District, Bone Regency? And how are the results of moral learning implemented in the formation of discipline in the class of students at MTs Daarul Qur'an Pajalele, Tellusiatinge District, Bone Regency? To answer these problems, researchers conducted qualitative research with educational, psychological, and sociological approaches. The data collection methods are in the form of interviews, observation, and documentation. Meanwhile, data analysis is carried out in inductive, deductive, and comparative forms. The results of the research show that the implementation of Aqidah Akhlak learning outcomes in the formation of discipline in the class of students at MTs Daarul Qur'an Pajalele, Tellusiatinge District, Bone Regency, is not significant. Because student discipline in class is still lacking, for example, arriving late, still talking when the teacher explains, and there are still students who are late entering when the bell rings. Meanwhile, one of the objectives of learning Aqidah Akhlak is to form the character of students who are obedient and respectful to teachers.